2012
DOI: 10.1002/dc.22893
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic vacuolization: An under‐recognized cytomorphologic feature in endocrine tumors of the pancreas

Abstract: The diagnosis of pancreatic endocrine neoplasm (PEN) is often straightforward; however, cytomorphologic variants may impose a diagnostic challenge, particularly in small biopsies such as fine-needle aspiration (FNA). Here we describe prominent fine cytoplasmic vacuoles in three cases of PENs which were initially evaluated by endoscopic ultrasound-guided FNA. The clinicopathologic features and diagnostic pitfalls of this cytomorphologic variant were discussed. Awareness of this rare cytomorphologic feature with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…In one case, PanNET was cytologically misdiagnosed as adenocarcinoma, for the most part because of the presence of cohesive groups of tumor cells with significant nuclear atypia and anisonucleosis. Although the majority of cases of PanNET demonstrate classic cytologic features, rare cases with significant variation in nuclear size and vacuolated cytoplasm did occur and have been reported in the literature . Under these circumstances, it would be important to obtain sufficient material for a cell block on which immunocytochemical stains with neuroendocrine markers, such as chromogranin and synaptophysin, could be performed to confirm the diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…In one case, PanNET was cytologically misdiagnosed as adenocarcinoma, for the most part because of the presence of cohesive groups of tumor cells with significant nuclear atypia and anisonucleosis. Although the majority of cases of PanNET demonstrate classic cytologic features, rare cases with significant variation in nuclear size and vacuolated cytoplasm did occur and have been reported in the literature . Under these circumstances, it would be important to obtain sufficient material for a cell block on which immunocytochemical stains with neuroendocrine markers, such as chromogranin and synaptophysin, could be performed to confirm the diagnosis …”
Section: Discussionmentioning
confidence: 99%
“…In summary, PanNET is an uncommonly diagnosed entity on cytology, and variants are even less frequently encountered. In our review, we identified only one prior case of pigmented PanNET diagnosed by FNA and only seven reports (ten cases) of FNA‐diagnosed clear cell PanNET . Metastases to the pancreas are also infrequently encountered in EUS‐FNA material, being far less common than primary pancreatic tumors .…”
Section: Discussionmentioning
confidence: 99%
“…The cytoplasm usually is moderate in amount and is pale, granular, or amphophilic. Cytoplasmic vacuoles are uncommon and if present, they are not prominent . Due to rich vascularity of neuroendocrine tumors, capillaries that traverse in‐between the tumor cells are not uncommonly seen.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor cells were positive for AE1/AE3, synaptophysin, and chromogranin. Recently, Levy et al reported the presence of cytoplasmic vacuolization as an under‐recognized cytomorphologic feature in PET . The authors reported three cases of PET having small distinct cytoplasmic vacuoles on cytology smears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation